Marginality and Integrative Management Positions - Ziller, Robert C.; Stark, Birgit; Pruden, Henry O. (Academy of Management Journal, 1969)
The marginality component of personality appears appropriate for men who hold integrative management positions. Research reveals an association between the Self-Other Orientation measure of marginality and two marginal occupations. Marginality suggests open-mindedness and other favorable attributes of integrators.